2019
DOI: 10.1097/md.0000000000016812
|View full text |Cite
|
Sign up to set email alerts
|

The association between CKD-associated pruritus and quality of life in patients undergoing hemodialysis in Pakistan

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
2
20
1
4
Order By: Relevance
“…The DOPPS recruited 51 062 participants from 21 countries across five study phases (DOPPS 1–5) between 1996 and 2015 [ 10 ] and 23 264 participants across DOPPS 4–6 between 2009 and 2018 [ 11 ]. Patients were asked to self-report via questionnaire the presence and severity of pruritus over a 4-week period.…”
Section: Epidemiology Of Ckd-apmentioning
confidence: 99%
See 2 more Smart Citations
“…The DOPPS recruited 51 062 participants from 21 countries across five study phases (DOPPS 1–5) between 1996 and 2015 [ 10 ] and 23 264 participants across DOPPS 4–6 between 2009 and 2018 [ 11 ]. Patients were asked to self-report via questionnaire the presence and severity of pruritus over a 4-week period.…”
Section: Epidemiology Of Ckd-apmentioning
confidence: 99%
“…The proportion of patients with moderate to extreme itch in DOPPS 1 and 2 (45 and 42%, respectively) was similar to that in DOPPS 4–6, where the overall prevalence of moderate to extreme itch was 37%, with no significant difference across study phases [ 8 ]. One reported difference was that participants noted less severe itch in DOPPS 5 (2012–2015) compared with DOPPS 1 (1996–2001) [ 10 ], which may suggest improvements in managing CKD-aP over time. A study of the Japanese DOPPS cohort (JDOPPS) showed that overall, 44% of patients experienced moderate to extreme pruritus, but the prevalence varied widely across centres, ranging from 20% to 70% [ 17 ].…”
Section: Epidemiology Of Ckd-apmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several previous studies have acknowledged similar patient profiles. 4 , 10 , 15 , 16 Therefore, those on treatment for a longer time are assumed to have better discipline in observing the schedule, despite some impending obstacles. This disposition resulted from the benefits perceived from participating in therapy sessions.…”
Section: Discussionmentioning
confidence: 99%
“…STS can cause side effects, such as severe but transient nausea and vomiting [50]. Mild hypernatremia, hypokalemia, or hypocalcemia (not significant) or a mild increase in the corrected QT interval (not significant) might also be side effects [51]. Another study demonstrated that neither potassium nor sodium accumulated in the circulating blood when STS was infused in conjunction with HD [52].…”
Section: Discussionmentioning
confidence: 99%